Effects of temperature and pH on the synthesis of nanohydroxyapatite powders by chemical precipitation - ALTAN, ERAY; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (My University, 2023)
Bone tissue engineering is based on a comprehensive understanding of bone structure, bone mechanics, and biology. In order to create nanostructured hydroxyapatite powders with customized properties, many synthesis strategies such as wet chemical precipitation, sol-gel, hydrothermal, and biomimetic approaches have been intensively researched through the years. Calcium phosphate (CaP)-based ceramic nanoparticles, including hydroxyapatite (HAp), were synthesized by the chemical precipitation technique at pH ranges of 7 to 11 and different calcination temperatures of 600 to 1100 °C. The synthesized powders were characterized by several techniques, including scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), energy dispersive X-ray analysis (EDX), and in vitro cell culture assays. The particle size analysis and zeta potential of these powders were also carried out using the dynamic light scattering (DLS) and laser Doppler electrophoresis methods. The results showed that the pH levels of 9 to 11 range and calcination temperatures of 600 to 800 °C were adequate for appropriate nanohydroxyapatite powder production using this method. The particle size of the nanohydroxyapatite was approximately 55 nm, although they were agglomerated after calcination. The biocompatibility tests demonstrated that these nanohydroxyapatite (nHAp) powders produced have appropriate cytocompatibility and can be used for bone graft production and other biomedical applications.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, CERAMICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; Materials Chemistry; Bioceramics; Bone grafts; Hydroxyapatite; Nanoparticles; Wet chemical precipitation